Answer: The number is: "2" . _______________________________________________________ The expression is: 2 − (½)x = (½)<span>x ; </span>→<span> in which "x" is the "unknown number". </span>_______________________________________________________ Explanation: ______________________________________________________ Given: _________________________________________________________ "Two decreased by a half of a number is one-half<span> of the number" ;
Let "x" represent the "unknown number" for which we wish to solve;
Write the expression as: _________________________________________________ " </span>2 − (½)x = (½)x " . _________________________________________________ Note: Add "(½)x" to EACH SIDE of the equation: _________________________________________________ 2 − (½)x + (½)x = (½)x + (<span>½)</span>x ;
to get: _________________________________________________ → 2 = 1x ;
↔ 1x = 2 ;
↔ x = 2 . _________________________________________________ Answer: The number is: " 2 " . _________________________________________________